Calprotectin and calgranulin C serum levels in bacterial sepsis - Bartáková, Eva; Štefan, Marek; Stráníková, Alžběta; Pospíšilová, Lenka; Arientová, Simona; Beran, Ondřej; Blahutová, Marie; Máca, Jan; Holub, Michal (Diagnostic microbiology and infectious disease, 2019)
The aim of this study was to evaluate the serum levels of calprotectin and calgranulin C and routine biomarkers in patients with bacterial sepsis (BS). The initial serum concentrations of calprotectin and calgranulin C were significantly higher in patients with BS (n = 66) than in those with viral infections (n = 24) and the healthy controls (n = 26); the level of calprotectin was found to be the best predictor of BS, followed by the neutrophil-lymphocyte count ratio (NLCR) and the level of procalcitonin (PCT). The white blood cell (WBC) count and the NLCR rapidly returned to normal levels, whereas PCT levels normalized later and the increased levels of calprotectin, calgranulin C, and C-reactive protein persisted until the end of follow-up. Our results suggest that the serum levels of calprotectin are a reliable biomarker of BS and that the WBC count and the NLCR are rapid predictors of the efficacy of antimicrobial therapy.
Keywords: Leukocyte L1 Antigen Complex; Neutrophil-lymphocyte count ratio; mužské pohlaví; Male; senioři; leukocytární L1-antigenní komplex; Calprotectin; C-reaktivní protein; Virus Diseases; Female; Humans; Calgranulin C; protein S100A12; White blood cell count; lidé; Lymphocyte Count; Procalcitonin; Middle Aged; ženské pohlaví; lidé středního věku; Bacterial Infections; neutrofily; Kinetics; senzitivita a specificita; bakteriální infekce; C-Reactive Protein; Biomarkers; biologické markery; kinetika; Sepsis; počet lymfocytů; Neutrophils; počet leukocytů; Leukocyte Count; dospělí; Adult; Sensitivity and Specificity; sepse; S100A12 Protein; Aged; virové nemoci